Preference of insects for different colors of sticky traps in rose apple (Syzygium aqueum) orchards / Muhammad Azeem Zuhaimi ... [et al.] - Zuhaimi, Muhammad Azeem; Abd Latip, Nurul Fatihah; Abdullah, Mohammad Azizi; Hasmi, Nur Atirah; Abdul Razak, Muhammad Irham; Muhammad Nasir, Dzulhelmi (Faculty of Applied Sciences, 2024)
Sticky traps are used to monitor various types of insects as one of the effective Integrated Pest Management (IPM) strategies. Integrated Pest Management provides an easy method for estimating the population density of pests that require low-cost, less skilled work and helps develop an environmentally friendly control strategy. However, different colors of sticky traps may have different preferences for insects collected in a specific area. Therefore, a study was conducted to determine whether the different colors of sticky traps influenced the diversity of insects collected in the UiTM Perlis farm. Sampling was performed each month in the Syzygium aqueum plot, four for each color of the sticky trap, from January to February 2019. A total of six different colors of sticky traps (red, blue, yellow, green, brown, and white) were randomly hung under the tree's canopy at 1 m height above ground level. The diversity of insects was collected every three days. The result shows a significant difference between the color of the sticky trap and the insect's diversity, in which the yellow sticky trap attracts the highest number of insects. Diptera was found to be the most abundant insect on a yellow sticky trap, while Mantodea was the lowest and only trapped on the white sticky trap. However, an in-depth study is needed to determine the relationship between insect diversity and rose apple production.